Comparative evaluation of micro-tensile bond strength between zirconia core and all-ceramic layering with different surface treatments: an in vitro study - Surya , Kiran Yadavilli; Anitha, Kuttae Viswanathan; Alekhya, Ghandikota (International Journal of Dental Materials, 2021)
Background: The quest for newer and stronger materials for replacing teeth has resulted in Zirconium oxide's introduction, which possesses excellent mechanical strength and toughness. However, uncertainty exists in the relationship between its bond strength and surface treatment method adopted and the mode of failure at the interface.Aim - The study aimed to evaluate the comparison of micro-tensile bond strength between the zirconia core and all-ceramic layering with different surface treatments and analyse their failure mode by Scanning Electron Microscope (SEM).Materials and methods: Zirconia cores (Ceramill ZI 71 XS) were fabricated by CAD-CAM into discs with 5mm diameter and 3.5mm height. Then the cores were divided into four groups. Among which, Group-I was the control group, and the remaining are surface treated. Group-II specimens were treated with sandblasting, followed by acid etching; Group-III and Group-IV were treated with zirliner and glass beads, respectively. After that, the veneering material (IPS Empress, E.max Ceram Dentin) of 2×2 mm was adhered to the zirconia core and then kept in the ceramic furnace. The specimens were mounted on a Universal Testing Machine, and tensile stress is applied. The obtained data were subjected to One-way ANOVA and Tukey-HSD tests for statistical analyses.Results - The samples treated with sandblasting followed by acid etching showed more micro-tensile bond strength between core and veneer interface. Furthermore, the SEM study revealed a cohesive failure in Group-II, whereas, in Group-I and -III, there was an adhesive failure. Group-IV specimens exhibited a mixed failure. One-way ANOVA showed significant differences (p=0.001) within the groups. In posthoc analysis, Group-III showed significant differences with Groups -I, II, and IV.Conclusion: Increased surface roughness of zirconia obtained by sandblasting with aluminium oxide particles, when coupled along with chemical etching with hydrofluoric acid, enhanced the micro-tensile bond strength between the Y-TZP zirconia core and veneering ceramic.